Use of a mobile tower‐based robot—The initial Xi robot experience in surgical oncology. Issue 1 (25th November 2015) - Yuh, Bertram; Yu, Xian; Raytis, John; Lew, Michael; Fong, Yuman; Lau, Clayton
Abstract : Background and Objectives: The da Vinci Xi platform provides expanded movement of the arms relative to the base, theoretically allowing increased versatility in complex multi‐field or multi‐quadrant surgery. We describe the initial Xi experience in oncologic surgery at a tertiary cancer center. Methods: One hundred thirty unique robot‐assisted procedures were performed using the Xi between 2014 and 2015, 112 of which were oncology surgeries. For procedures involving multiple quadrants, the robot was re‐targeted. Complications were assessed according to Martin criteria and the Clavien–Dindo classification up to 90 days after operation. Results: Thirteen different operations were performed in five oncology subspecialties (urology, gynecology, thoracic, hepatobiliary, and gastrointestinal surgery). Median operative times ranged from 183 min for nephroureterectomy to 543 min for esophagogastrectomy. Median estimated blood loss did not exceed 200 ml for any of the categorized procedures . No patients were transfused intraoperatively and no positioning injuries occurred. Conversions to open operation occurred in three cases (2.7%), though not related to complications or technical considerations. Overall complication rate was 26% with major complication rate of 4%. Readmissions were necessary in 11 (10%) patients. Conclusions: The da Vinci Xi can be safely assimilated into a surgical oncology program. The Xi offers versatility to various oncologic procedures with satisfactory complication and readmission rates. J. Surg. Oncol. 2016;113:5–7 . © 2015 Wiley Periodicals, Inc.